Diedrich Diederichsen, Aesthetics of Pop Music (Cambridge: Polity Press, 2023). ISBN: 1509552030, 176 pp, €9.99 (paperback). (Journal of the Society for Musicology in Ireland, 2023)
A review of Diedrich Diederichsen, Aesthetics of Pop Music (Cambridge: Polity Press, 2023). ISBN: 1509552030, 176 pp, €9.99 (paperback).